0D/1D Z-scheme g-C3N4 quantum dot/WO3 composite for efficient Cr (VI) photoreduction under visible light. Issue 4 (August 2021) - Zhou, Jie; Cai, Wenyi; Ding, Jing; Wan, Hui; Guan, Guofeng
Abstract: The appropriate construct of Z-scheme heterostructure composite with high photocatalytic activity has created new opportunities for environmental protection. Herein, graphitic carbon nitride quantum dots/tungsten trioxide (CNQDs/WO3 ) was firstly fabricated using CNQDs decorated onto the surface of WO3 nanorod grown along the [110] orientation in hydrothermal environment to construct a Z-scheme heterostructure composite. By various characterization methods, the crystal structure, micro morphology, atomic valence state and surface functional groups of the catalyst were systematically revealed. The results indicated that Z-scheme heterojunctions between CNQDs and WO3 were successfully constructed. Compared with pure WO3, CNQDs/WO3 exhibited prominent photoreduction performance under visible light irradiation. The optimal 5% CNQDs/WO3 could reduce almost 100% Cr (VI) under acidic condition with the best photocatalytic activity within 90 min. More than this, 5% CNQDs/WO3 also displayed excellent stability and recyclability even after five cycles of photoreduction experiments. Based on the free radical quenching experiments, the possible photoreduction reaction mechanism had been proposed in detail. The Z-scheme heterostructure provided the possibility of the generation, rapidly transfer and efficient separation of photogenerated electrons, which were major active species in the Cr (VI) photoreduction process. Graphical Abstract: ga1 Highlights: 0D/1D Z-scheme heterojunction composite CNQDs/WO3 has been constructed. The Z-scheme heterojunction structure improved the separation and transfer of photogenerated electrons efficiently. CNQDs/WO3 exhibited excellent activities in Cr (VI) photoreduction.